Unraveling the impact of social media on accounting information disclosure: does government supervision matter? - Jackie Zhanbiao Li; Saeed Awadh Bin-Nashwan; Yingqian Lao; Chai Lee Goi; Yew Hua Ling (Humanities & Social Sciences Communications)
Abstract The growing influence of social media plays a pivotal role in enhancing corporate governance capabilities, thereby contributing to the quality of accounting information disclosure. Relying on a large sample comprising 19,889 A-share listed companies on the Shanghai and Shenzhen Stock Exchanges in China, spanning the period from 2012 to 2022, this research aims to empirically assess the impact of social media on accounting information disclosure of Chinese-listed companies while also investigating the moderating effect of government supervision. We found a positive relationship between increased social media usage and the heightened quality of accounting information disclosure. Specifically, a rise in negative coverage within social media is associated with a more substantial improvement in the quality of corporate accounting information disclosure. Furthermore, when social media usage attracts the moderating effect of government supervision, the positive impact on enhancing the quality of corporate accounting information disclosure becomes more evident. This research contributes theoretically by enriching existing research on the relationship between social media, government supervision, and accounting information disclosure. In practical terms, it serves as a valuable reference for fostering the healthy development of China’s capital market.